Characterisation of new reference materials IAEA‐610, IAEA‐611 and IAEA‐612 aimed at the VPDB δ13C scale realisation with small uncertainty. (18th February 2021) - Assonov, Sergey; Fajgelj, Ales; Hélie, Jean‐François; Allison, Colin; Gröning, Manfred
Abstract : Rationale: LSVEC, the second anchor Reference Material (RM) for the VPDB δ 13 C scale realisation, was introduced in 2006. In 2015, its δ 13 C value was found to be drifting and, in 2017, its use as an RM for δ 13 C was officially discontinued by IUPAC. New RMs of low uncertainty are needed. This paper describes the preparation and characterisation of IAEA‐610, IAEA‐611 and IAEA‐612 (calcium carbonate, of chemical origin) which shall serve as a set of RMs aimed at anchoring the VPDB scale at negative δ 13 C values. Methods: The preparation and characterisation of IAEA‐610, IAEA‐611 and IAEA‐612 were performed by addressing the contemporary technical requirements for RM production and characterisation (ISO Guide 35:2017). The three RMs were produced in large quantities, and the first batch was sealed into ampoules (0.5 g) to ensure the integrity of the RM during storage; additional batches were sealed for long‐term storage. The most accurate method of CO2 preparation and stable isotope measurements was used, namely carbonate‐H3 PO4 reaction under well‐controlled conditions combined with well‐tested stable isotope ratio mass spectrometry. Results: The assigned values of δ 13 C and associated uncertainties are based on a large number of analyses ( 10 mg aliquots) performed at IAEA and address all the known uncertainty components. For aliquots down to 100 μg, the δ 13 C uncertainty is increased. The uncertainty components considered are as follows: (i) material homogeneity, (ii) value assignment against IAEA‐603, (iii) potential storage effects, (iv) effect of the 17 O correction, and (v) mass spectrometer linearity and cross‐contamination memory in the ion source. Conclusions: The new RMs IAEA‐610, IAEA‐611 and IAEA‐612 have been characterised on the VPDB δ 13 C scale in a mutually consistent way. The use of three RMs will allow a consistent realisation of the VPDB δ 13 C scale with small uncertainty to be established, and to reach metrological compatibility of measurement results over several decades.